1992
DOI: 10.1111/j.1600-0447.1992.tb03214.x
|View full text |Cite
|
Sign up to set email alerts
|

Posterior fossa abnormalities in major depression: a controlled magnetic resonance imaging study

Abstract: High-field magnetic resonance (MR) images were used to study posterior fossa morphology in 27 patients with major depression and 36 normal control subjects. Depressed patients demonstrated smaller brain stem and cerebellar vermis than controls. These differences were highly significant for the anterior cerebellar vermis and medulla. There was also a striking age-related decline in midbrain size in depressed patients as well as in controls. Our results are consistent with several lines of evidence implicating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 19 publications
0
32
0
1
Order By: Relevance
“…The number of previous episodes of depression may be largely associated with the smaller V3 area in multiple-episode patients, but this requires future study. Others (Shah et al 1992) found that depressed patients have smaller anterior, posterior and total vermal areas compared to healthy volunteers. Vermal area 3 consists of the inferior posterior lobe and nodulus (flocculonodular lobe) of the vermis.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The number of previous episodes of depression may be largely associated with the smaller V3 area in multiple-episode patients, but this requires future study. Others (Shah et al 1992) found that depressed patients have smaller anterior, posterior and total vermal areas compared to healthy volunteers. Vermal area 3 consists of the inferior posterior lobe and nodulus (flocculonodular lobe) of the vermis.…”
Section: Discussionmentioning
confidence: 97%
“…Effect size was based on the F -value obtained from the ANCOVA using the formula f ϭ ͙ (k-1)F/N (Cohen 1977). A multiple regression analysis was preformed to assess the variables that based on previous studies would be hypothesized to contribute to small vermal size specifically, number of previous episodes of depression (Shah et al 1992;Escalona et al 1993), lithium exposure (Donaldson and Cuningham 1983;Kores and Lader 1997) and history of substance abuse (Aasly et al 1993). Other analyses were performed as necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even a small change in the dimensionality of a single landmark, in the course of evolution, has capacity to redirect the dimensionality of all the skull landmarks, and hence to create a different data set of measurements for inter-landmark distances (3). Although, such a re-modeling of the human skull may not always result in a functional gain and may predispose individuals to certain neuropsychiatric disorders (8,20,21), as a cost to the evolutionary benefits of the survival (22)(23)(24).…”
Section: Evolutionary Aspectmentioning
confidence: 99%